TRANSNATIONAL VISUAL INQUIRY: ARAB WOMEN’S INTERDEPENDENT/INDEPENDENT MOVES ON TIKTOK AND INSTAGRAM - Hurley, Zoe (AoIR Selected Papers of Internet Research, 2021)
This study addresses the complex matrix of gendered visual interdependence/ independence of Arab women social media influencers, defined as micro-celebrities generating digital incomes. It takes Instagram and TikTok, image and video sharing platforms, as a case to illustrate examples of Arab women’s curated visual identities. The study synthesises feminist transnationalism and visual inquiry. Transnationalism refers not only to the movement and exchanges of consumer items, languages, practices and peoples across national borders, but it is also a research agenda concerned with the situated perspectives of social actors backgrounded by mainstream scholarship. Feminist transnationalism is synthesised with ‘inquiry graphics’ as a semiotic move to ask critical questions about images. This offers a unique contribution to feminist visual social media scholarship, both contextually and theoretically. The study reveals Arab women’s positionalities as occurring in simultaneously interdependent and independent relationships to commercial Western practices. Examples include the influencer @amyroko, from Saudi Arabia with 1.5 million followers, who wears a niqab (facial veil) as she promotes make-up brands while never showing her face online. @amyroko’s posts are mediated via TikTok and Instagram’s affordances for synthetic embodiment and involve remixing American rap, hip-hop, reggaeton beats, her own dance moves and defiant stance of Arab feminist positionality. However, this is not a form of cultural appropriation but a reconfiguration of localised subjectivities. Overall, theorising reveals Arab women’s curatorial identities as consecutively interdependent/ independent within broader hyper-inequalities, systemic and local patriarchal oppression. This disrupts fixed conceptions of Arab women’s positionalities and goes beyond theoretical essentialism.